Civil society structures in Ukraine: formation and development in the latter half of 16th to 19th centuries - Panfiłova, Tatiana (Studia Europaea Gnesnensia, 2016)
Based on the sources and critical consideration of historiography of the problem, the author defines regularities and specific features of the formation of structures of Ukrainian civil society, as a factor which bolstered Ukrainian national idea.